Protein quality of commercially important edible bivalves - Jingjing Song; Cong Luo; Lim, Leong Seng; Cheong, Kit Leong; Ardavan Farhadi; Karsoon Tan (Taylor & Francis, 2024)
Bivalves are a high-quality source of animal protein for human consumption. In recent years, the demand for bivalve proteins has increased dramatically, leading to a sharp increase in global production of marine bivalves. To date, although the amino acid profiles of many bivalves have been reported, such information has not been well organized. Therefore, there is an urgent need for a comprehensive scientific review of the protein quality of bivalves, especially commercially important edible bivalves. In this context, this study was conducted to evaluate the protein quality of commercially important edible bivalves. In general, most bivalves are rich in protein (> 50% of their dry weight) and amino acids (> 30g/100g protein). Although most species of bivalves are rich in essential amino acids (EAA) (up to 50g/100g protein), some species of edible bivalves have very low levels of EAA (< 5g/100g protein). Based on the AA score, almost all bivalves have at least two limiting AAs. Most bivalve proteins provides delicious flavors with unami, sweetness and a hint of bitterness. The findings of this study not only serve as a a guide for selecting appropriate bivalves based on consumer preferences for specific AAs or AA scores, but also provide information on potential bivalve species for aquaculture to produce higher protein quality to meet the growing demand for high quality animal protein.